Menjelajahi Pembelajaran Kooperatif: Konsep dan Implikasi - Zaharatunnisa, Zaharatunnisa; Sari, Rita (Mulya Literasi Publishing, 2023)
The importance of collaboration in the current era of Society 5.0 must certainly be linked to learning. The purpose of writing this article is to describe the essence of the collaborative approach from David W. Johnson's point of view. The method used is literature research. The result of the research confirms that the concept of interdependence emphasizes the importance of cooperation and the contribution of each team member in achieving common goals, while shared responsibility encourages active, proactive, and responsible participation in the learning process. Therefore, cooperative learning can stimulate academic achievement and develop social skills in a balanced manner, thus paving the way for comprehensive and collaborative learning.